Solar panel tracker model using PIC16F877A - Noor Kamal, Noralif Khairrurijaal (2005)
The aim of this project is to develop a model of a solar panel tracker module using Peripheral Interface Controller (PIC). This paper presents an application of a solar panel tracker module that measures the output voltage of solar panel in Photovoltaic (PV) application and tracks the sun's movement in order to get optimum exposure of the sun's irradiance. The tracking method is based on comparing the output voltages of each solar cell in the solar panel. The solar panel tracker module will rotate the panel until both output voltages of solar cells are equal. In the experiment, PIC's Analogue to Digital conversion manages to convert the analogue input from solar cell into its digital form. However, the PIC controlled servomotor is not functional due to wrong choice of motor and mechanical design. Moreover, the Liquid Crystal Display (LCD) cannot display the value of output voltage from solar cell. It only manages to display "voltage" preset by program. This is due to look-up table's algorithm for Analog to Digital Conversion (ADC) to LCD conversion. All results obtained from this study would be beneficial to the PV application engineers for future planning and monitoring purposes.